The Role of Islamic Finance in Promoting The Development of Tadika Al-Fikh Orchard Kuala Lumpur - Nabilah, Juwita Putri; Amalia, Alfi (Universitas Muhammadiyah Surabaya, 2024)
Islamic finance plays a crucial role in education within the expanding global landscape of Islamic economics. It has been widely observed that Sharia-compliant financial institutions wield significant influence over the educational framework at Tadika AL-Fikh Orchard Kuala Lumpur. This study endeavors to assess the impact of Sharia finance in fostering the advancement of Tadika AL-Fikh Orchard Kuala Lumpur. The objective is to illuminate the pivotal role of Islamic finance in enhancing early childhood education by facilitating the delivery of morally grounded teachings and fostering a holistic comprehension of Islamic financial literacy. Moreover, it aims to provide motivational support and promote an in-depth understanding of Islamic financial principles. The significance of employing Sharia-compliant school finance policies, tailored to collaborative efforts with financial institutions such as BTM, BMT, and both Sharia and conventional banks, is underscored. Additionally, participants are encouraged to contribute their insights and perspectives, initiating steps to provide educational materials and practical exercises aimed at elevating comprehension levels, practical applications, and successful outcomes in Sharia finance.